2019
DOI: 10.1176/appi.ajp.2018.17101147
|View full text |Cite
|
Sign up to set email alerts
|

Connectome-Based Prediction of Cocaine Abstinence

Abstract: Objective: To identify a brain-based predictor of cocaine abstinence using a recently developed machine learning approach, connectome-based predictive modeling (CPM). CPM is a predictive tool and a method of identifying networks that underlie specific behaviors ('neural fingerprints'). Methods: Fifty-three individuals participated in neuroimaging protocols at the start of treatment for cocaine-use disorder, and again at the end of 12-week treatment. CPM with leave-one-out cross-validation was run to identify p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(151 citation statements)
references
References 42 publications
8
127
1
3
Order By: Relevance
“…Other imaging studies have used topological approaches to characterize how PTSD impacts neural networks 20,21 , and recent work suggests the utility of using machine learning approaches to predict and potentially identify those at risk for PTSD 22 . This area of inquiry has already significantly advanced the field in psychosis research and substance use, where machine learning can now identify patients using brain-based pathology 23 and individualized treatment response 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Other imaging studies have used topological approaches to characterize how PTSD impacts neural networks 20,21 , and recent work suggests the utility of using machine learning approaches to predict and potentially identify those at risk for PTSD 22 . This area of inquiry has already significantly advanced the field in psychosis research and substance use, where machine learning can now identify patients using brain-based pathology 23 and individualized treatment response 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…To model the RSFC‐phenotype association, four regression algorithms including connectome‐based predictive modeling (CPM), support vector regression (SVR), least absolute shrinkage and selection operator (LASSO), and Ridge regression have been frequently adopted for their good performances and interpretabilities (Coloigner, Phlypo, Bush, Lepore, & Wood, ; Cui & Gong, ; Dadi et al, ; de Vos et al, ; Gao, Greene, Constable, & Scheinost, ; Jiang et al, ; Meng et al, ; Ryali, Chen, Supekar, & Menon, ; Shen et al, ; Toiviainen, Alluri, Brattico, Wallentin, & Vuust, ). CPM is in fact a linear regression model and has been successfully applied in predicting intelligence (Beaty et al, ; Finn et al, ; Jiang et al, ), attention (Rosenberg, Finn, Scheinost, Constable, & Chun, ), cocaine abstinence (Yip, Scheinost, Potenza, & Carroll, ), and reading comprehension (Jangraw et al, ). SVR implements space transformation by some kernel function in order to achieve better prediction (Basak, Pal, & Patranabis, ), and has been utilized in prediction of mental disease (Rizk‐Jackson et al, ), brain maturity (Dosenbach et al, ; Nielsen et al, ), and painful sensation (Tu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, imposing a movement threshold in this sample, a relatively common procedure to limit the impact of motion on functional connectivity analyses (e.g. [47, 48, 50]), revealed that the formal mock scan group had more low-motion data relative to the informal mock scan group.…”
Section: Resultsmentioning
confidence: 99%
“…If a participant’s scan had a mean FFD above a threshold, it was designated as a “high motion” scan; if it was below the threshold, it was considered a “low motion” scan. Mean FFD thresholds of 0.10, 0.15, and 0.20 mm were used, as thresholds of this magnitude have been shown to limit the impact of motion [25, 47] while allowing for sample sizes of adequate size in children/adolescents [47, 48] and in those with a disorder [10, 49, 50].…”
Section: Methodsmentioning
confidence: 99%